Lane‐changing trajectory planning method for automated vehicles under various road line‐types. Issue 1 (2nd March 2020) - Wang, Ying; Wei, Chong; Liu, Erjian; Li, Shurong
Abstract : This study proposes a lane‐changing trajectory planning method for automated vehicles under various road line‐types. The method uses the polynomial regression model to describe the road line‐types, and then a non‐linear optimisation model is constructed to generate the lane‐changing trajectory based on the road polynomial functions. The process of connecting the lane‐changing manoeuvre with the car‐following manoeuvre is discussed in this study, which ensures the ride comfort of the ego vehicle after the lane‐changing manoeuvre. Moreover, considering that the lag vehicle on the target lane may be affected by the lane‐changing manoeuvre, the situation that the lag vehicle maintains the car‐following manoeuvre with the ego vehicle is taken into account in the authors' model. Another small innovation is that they have designed a simple and effective method to find the suitable initial guess for the proposed non‐linear optimisation model. The simulation results show that the lane‐changing trajectory generated by the proposed model is smooth and continuous, and the automated vehicle can avoid potential collisions efficiently during the lane‐changing process. In emergent conditions, the proposed model can also plan the corrected trajectory to ensure safety.